2019
DOI: 10.12688/f1000research.19739.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Buccal administration of hydrogen-producing blend after a mild traumatic brain injury in a professional athlete

Abstract: Background: Sport-related mild traumatic brain injury (TBI) is a serious trauma that could impair brain function of an injured athlete. Treatment solutions for mild TBI typically concentrate on complete rest, while non-traditional therapeutic options remain largely ineffective. Molecular hydrogen (H2) is an innovative neuroprotective agent that can easily reach the brain, yet no data are available concerning its value as a first-aid intervention after a mild TBI. Case report: This case report demonstrates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For instance, hydrogen improved the brain MRI indices in the acute brain stem infarct sites (Ono et al, 2011), positively affected patientreported scores in Parkinson's disease (Yoritaka et al, 2013), attenuated the stroke severity in patients with cerebral infarction (Ono et al, 2017), increased mood, anxiety, and autonomic nerve function in healthy volunteers (Mizuno et al, 2018), reduced the presence and severity of symptoms of mild traumatic brain injury (Javorac et al 2019), and improved cognitive function in community-dwelling older women (Korovljev et al, 2020). Although those studies showed promising results of medium-to long-term intervention with hydrogen on various indices of brain function, few trials endeavored to evaluate short-term effects of hydrogen on brain performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, hydrogen improved the brain MRI indices in the acute brain stem infarct sites (Ono et al, 2011), positively affected patientreported scores in Parkinson's disease (Yoritaka et al, 2013), attenuated the stroke severity in patients with cerebral infarction (Ono et al, 2017), increased mood, anxiety, and autonomic nerve function in healthy volunteers (Mizuno et al, 2018), reduced the presence and severity of symptoms of mild traumatic brain injury (Javorac et al 2019), and improved cognitive function in community-dwelling older women (Korovljev et al, 2020). Although those studies showed promising results of medium-to long-term intervention with hydrogen on various indices of brain function, few trials endeavored to evaluate short-term effects of hydrogen on brain performance.…”
Section: Discussionmentioning
confidence: 99%
“…alertness, brain metabolism, choline-to-creatine ratio, hydrogen, sleep (Ohta 2012), HRW was found to ameliorate patient-reported scores in Parkinson's disease (Yoritaka et al, 2013), increase mood, anxiety, and autonomic nerve function in daily life (Mizuno et al, 2018) and reduce the presence and severity of symptoms of mild traumatic brain injury (Javorac et al 2019). The beneficial effects of dihydrogen in neurology are attributed to its role in neurometabolic processes, including bioenergetics, anti-oxygenation, anti-inflammation, and anti-apoptosis, (Iketani & Ohsawa, 2017;Ostojic, 2017).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…An athlete given a buccal administration of hydrogen producing dissolving tablet immediately and every 2 hours for a day after concussive injury presented with an improvement in concussion score from moderate to mild category. 57 In the future, larger clinical studies may provide more data on dose and efficacy of such therapies in the setting of TBI.…”
Section: H Ydrogen T Herapy I ...mentioning
confidence: 99%